MENEPIS PRADUGA KESULITAN MENGIDENTIFIKASI UNSUR-UNSUR CERPEN BERBASIS PROYEK BERBANTU APLIKASI WORDWALL - Maulidiah, Rina Hayati; Atmazaki, Atmazaki; Hayati, Yenni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: Literature learning, particularly in recognizing the elements of short stories, is often considered difficult by students. This explanation arises because the learning is still theoretical and does not provide space for real learning experiences. Project-based learning assisted by a wordwall application is an innovative alternative in Indonesian language learning to foster critical and creative thinking skills through real projects. This study aims to describe the effectiveness of identifying short story elements based on a project assisted by a wordwall application. The research method used is descriptive qualitative with data collection techniques through observation, distributing questionnaires, interviews, and documentation during the learning process. The results of the study indicate that identifying short story elements based on a project assisted by a wordwall application improves students' understanding of short story elements, such as theme, characters, plot, setting, and moral. In addition, students become more active, creative, and collaborative in learning activities. Thus, identifying short story elements based on a project assisted by a wordwall application is effective in overcoming the presumption of difficulty in learning short story elements.Keywords: Project-Based Learning, Identification of Short Story Elements, Wordwall Application  Abstrak: Pembelajaran sastra, khususnya dalam mengenal unsur-unsur cerpen, sering dianggap sulit oleh peserta didik. Penjelasan tersebut muncul karena pembelajaran masih bersifat teoritis dan kurang memberi ruang bagi pengalaman belajar yang nyata. Pembelajaran berbasis proyek berbantuan aplikasi wordwall menjadi alternatif inovatif dalam pembelajaran Bahasa Indonesia untuk menumbuhkan kemampuan berpikir kritis dan kreatif melalui proyek nyata. Penelitian ini bertujuan untuk mendeskripsikan efektivitas mengidentifikasi elemen-elemen cerpen berdasarkan proyek berbantuan aplikasi wordwall. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, penyebarab angket, wawancara, dan dokumentasi selama proses pembelajaran. Hasil penelitian menunjukkan bahwa mengidentifikasi unsur-unsur cerpen berbasis proyek berbantuan aplikasi wordwall meningkatkan pemahaman siswa terhadap unsur-unsur cerpen, seperti tema, tokoh, alur, latar, dan amanat. Selain itu, peserta didik menjadi lebih aktif, kreatif, dan kolaboratif dalam kegiatan pembelajaran. Dengan demikian, mengidentifikasi elemen-elemen cerpen berbasis proyek berbantuan aplikasi wordwall efektif digunakan untuk mengatasi praduga kesulitan dalam pembelajaran elemen-elemen cerpen.Kata Kunci: Pembelajaran Berbasis Proyek, Identifikasi unsur cerpen, Aplikasi wordwall